Pengembangan E-LKPD Berbasis Masalah untuk Meningkatkan Hasil Belajar Matematika - Meilina Putri Amelia Arifianti; Fitri Siti Sundari; Dendy Saeful Zen (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Students’ low mathematics achievement is attributed to the limited use of instructional media, teacher-centered instruction, and the use of worksheets that do not effectively encourage students to think actively when solving problems. This study aims to develop problem-based e-worksheets on data concepts, determine their feasibility, and test their effectiveness in improving the mathematics achievement of fifth-grade elementary school students. This study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 19 fifth-grade students at SDN Bojongkoneng 4 in Bogor Regency, one classroom teacher, and three expert validators. The research instruments included validation sheets from media experts, language experts, and content experts; response questionnaires for teachers and students; and learning outcome tests in the form of pretests and posttests. The validation results showed that the E-LKPD received a 98% approval rating from media experts regarding interactivity, ease of use, design appearance, and layout. It received a 100% rating from language experts in the aspects of language integration in problem-based learning, language clarity, and appropriateness for students, as well as a 94% rating from content experts in the aspects of conceptual accuracy, content completeness, content readability, and alignment of competencies—all meeting the “highly valid” criteria. Teacher responses received a 98% rating, and student responses received an 86% rating, both falling into the “very good” category. The N-Gain analysis result of 0.78 falls into the “high” category, indicating an improvement in students’ learning outcomes after using the E-LKPD. Thus, the problem-based E-LKPD is deemed feasible, practical, and effective for improving the mathematics learning outcomes of fifth-grade elementary school students.